Cardiac MRI right ventricle / left ventricle (RV/LV) volume ratio improves detection of RV enlargement. Issue 6 (9th December 2015) - Altmayer, Stephan P.L.; Patel, Amit R.; Addetia, Karima; Gomberg‐Maitland, Mardi; Forfia, Paul R.; Han, Yuchi
Abstract : Purpose: To determine the normal range of the ratio of right ventricular (RV) end‐diastolic volume to left ventricular (LV) end‐diastolic volume by magnetic resonance imaging (MRI) and examine whether combining this volume ratio with RVEDV indexed to body surface area (RVEDVi) increased the detection of RV dilation in patients with pulmonary arterial hypertension (PAH). Materials and Methods: MRI‐derived ventricular function and volumes were measured in a control group ( n  = 152) and in patients with PAH ( n  = 46). Images were acquired with a 1.5T Siemens or a 1.5T Philips scanner using a steady‐state free procession sequence. Proposed criteria for the detection of RV enlargement, including RVEDVi alone, RV/LV volume ratio alone, and combining both criteria, were evaluated in both groups. Results: The range (mean ± 2 standard deviations) for the volume ratio in the normal population was found to be 0.906–1.266; there was no difference between genders ( P  = 0.70). Combining this ratio with RVEDVi detected RV enlargement in 21.7% ( P  < 0.001) PAH patients (volume ratio ≥1.27) who were not identified by the RVEDVi alone (>104 mL/m 2 for females and >113 mL/m 2 for males). Conclusion: Combining RV/LV volume ratio with indexed RVEDV increased detection of RV enlargement in a PAH population. This result may have potential impact in RV size assessment. J. Magn. Reson. Imaging 2016;43:1379–1385.